Anti‐inflammatory potential of black carrot (Daucus carota L.) polyphenols in a co‐culture model of intestinal Caco‐2 and endothelial EA.hy926 cells. Issue 2 (13th December 2016) - Kamiloglu, Senem; Grootaert, Charlotte; Capanoglu, Esra; Ozkan, Ceren; Smagghe, Guy; Raes, Katleen; Van Camp, John
Abstract : The ability of polyphenol‐rich black carrot and its by‐products, i.e., peel and pomace, to modulate the inflammatory response in tumor necrosis factor‐α (TNF‐α)‐treated endothelial cells after gastrointestinal digestion and in a co‐culture of intestinal Caco‐2 and endothelial EA.hy926 cell model is determined. It is shown that the polyphenol‐rich black carrot absorption products may function through an inhibitory regulation of the inflammatory cascade in endothelial cells. Abstract : Scope: The present study was developed to determine the ability of polyphenol‐rich black carrot and its by‐products, i.e., peel and pomace, to modulate the inflammatory response in tumor necrosis factor α (TNF‐α) treated endothelial cells after gastrointestinal digestion and in a co‐culture of intestinal Caco‐2 and endothelial EA.hy926 cell model. Results: The results indicated that after 4 h of treatment, the transport of anthocyanins and phenolic acids was higher for digested samples (1.3−7%) compared to the undigested samples (0−3.3%). The transported polyphenols were able to downregulate the secretion of pro‐inflammatory markers, i.e. IL‐8, monocyte chemoattractant protein 1, vascular endothelial growth factor, and intercellular adhesion molecule 1, under normal and tumor necrosis factor α induced inflammatory conditions. The most pronounced protective effects were observed with digested samples under inflammatory conditions, which significantly decreased the secretion of all markers from 120−203% down to 34−144% ( p < 0.001). Conclusions: Overall, these results show that the polyphenol‐rich black carrot absorption products may function through an inhibitory regulation of the inflammatory cascade in endothelial cells.